Objeto de aprendizagem para compreensão do princípio da aposição local - Bezerra, Jéssica Tayrine Gomes de Melo (2014)
This research comes from the general hypothesis that Learning Objects (LOs) enable meaningful learning. To verify this hypothesis, a Learning Object was analyzed, it was developed for experimental psycholinguistics area, in order to facilitate the understanding of the Late Closure Principle, postulated by Garden-Path Theory. The Learning Objects are designed as reusable digital tools that facilitate learning, that are available over the Internet. Through the Learning Objects It is possible to simulate and study in an interactive and non-linear way. Being a non-traditional method, it provides an interesting research about the different styles of learning and, as a digital resource, provides an understanding of the use of technology in education and learning by natives and digital immigrants. To analyze the characteristics of the LO and relate them to the profiles of the participants, two questionnaires were applied to two classes of Linguistics Theories II discipline, in Letras undergraduate course, that get in touch with the content through a lecture and later explored the elements of LO. The results of the questionnaires allowed to characterize the technical and educational quality of the resource, since the survey participants positively assessed the potential of learning, usability and content. It was concluded that the analyzed learning object is characterized as a potentially significant material and, therefore, provides a meaningful learning of the Late Closure Principle because its resources were structured based on the principles of cognitive theory of meaningful learning that reflect the way how knowledge is organized in the cognitive structure of learners. Besides that, the participants identified as natives and digital immigrants and with different learning styles, performed well in the resolution of the analyzed activities, as well as showed interest in learning through learning objects. Thinking that way, the use of learning objects for understanding linguistic content in higher education is an issue that worth further investigation and it is still a challenge, as there is a need for greater availability of these resources.